Lessons in leadership executive leadership programs for advancing diversity in higher education - Leon, David Jess. (Amsterdam ; Oxford : Elsevier JAI, 2005)
A largely unseen phenomenon is shaping the direction of higher education today: the growth of leadership programs. These programs are hidden ladders that help the talented move up toward university presidencies. Their number and importance are rapidly increasing, and they will more and more determine who makes decisions in higher education. We need to know more about them. "Lessons in Leadership" is the first book to address them directly, highlighting their histories and achievements. In it, the directors of most major programs in the country describe their focus, curriculum, and participants' reactions. The book especially spotlights programs aimed at minorities, since they stand to benefit most from them and since their participation will likely have the greatest impact on U.S. higher education. This volume has three sections: Hidden Springboard - The Importance of Leadership Programs; The First Wave - Traditional Leadership Programs; and, The New Leaders - Programs Focused Entirely on Minorities. The first analyzes the rapid demographic changes occurring in American society and their consequences for higher education. The second looks at two of the major players in higher education leadership and describes the changes in the programs over the years. The third focuses on the latest entrants: programs created in part because of the lack of diversity in the traditional offerings. Although the new programs share many features with their older brothers, they provide special perspective on the challenges facing minority administrators in higher education. Leadership programs are an intriguing, important, half-concealed force in higher education today. "Lessons in Leadership" reveals them to a wider public.
Includes bibliographical references.
Description based on print version record.
Keywords: Educational leadership -- United States; Leadership -- Study and teaching -- United States; Minorities -- Education -- United States; Leadership -- United States; Higher & further education, tertiary education; Organization & management of education; Education, Higher